Quaternary Sedimentation in the St. Lawrence Estuary and Adjoining Areas, Eastern Canada: An Overview Based on High-Resolution Seismo-Stratigraphy - Syvitski, James; Praeg, Dan (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1989)
ABSTRACTThe regional Quaternary seismo-stratigraphy of NW Gulf of St. Lawrence, based on 5700 line km of high resolution seismic reflection profiles, is described. The Quaternary sequence can be locally missing or can exceed 1.3 km in thickness. Five major stratigraphic units are recognized, which vary in their character and distribution so that at any location a variety of bedrock types may be overlain by a distinctive Quaternary sequence. These units relate to the advance and retreat of the Late Wisconsinan Ice Sheet. We interpret these units as: Unit 1, recording the presence of grounded glacial ice, including ice-loaded and ice-deposited sediments. Unit 2, ice-proximal coarse-grained sediment deposited either as a thin, conformable layer during the rapid retreat of an ice terminus, or as a wedge-shaped fan marking the position of an ice front still stand. Unit 3, ice-distal fine-grained sediment deposited from meltwater plumes at times of elevated sea levels and rapidly ablating sea ice. Unit 4, paraglacial deltaic sediment marking the melting of terrestrially-based ice caps, and the concommittant growth of deltas, rapidly prograding into a seaway undergoing rapidly falling sea levels. Unit 5, postglacial sediment reflecting the winnowing of shallow areas and deposition of organic-rich mud in deep basins, under modern sea level and océanographie conditions. A conceptual model dealing with the deposition of sediment associated with the withdrawal of a continental ice sheet is developed. The model includes the dynamics associated with the initial ice advance, terminal ice dynamics, retreat of the ice terminus, stable ice-fronts during the recessional phase, ice sheets ablating on land, and postglacial sedimentation under conditions of fluctuating sea levels.